2019
DOI: 10.14744/megaron.2019.94840
|View full text |Cite
|
Sign up to set email alerts
|

Aktif yaşlanma sürecinin yerel ekonomi ile etkileşimi: Balıkesir üzerine bir araştırma ve sistem önerisi

Abstract: Teknoloji ve kentleşme günümüzün yaşam biçimini tasarlarken "yaşlanma" kavramı da kentlerin geleceğinde önemli bir değişken olarak yükselmektedir. Türkiye bugün genç nüfusa sahip olsa da, yaşam sürelerinin uzaması ve doğurganlık oranının azalması ile yaşlanmakta olan ülkeler içindedir. Hızla yükselen kentleşme (2000 yılında %65, 2015 yılında %92) ve değişim sürecindeki demografik yapının kent ekonomisi etkileşimi değerlendirilmesi gereken bir konudur. Söz konusu etkileşimin dikkat çeken stratejilerinden biri "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In addition, it is seen that they have tendency on the subjects such as; general health (Altunel & Kartal, 2019;Karadayı et al, 2019), care services (Çiftçi & Zelka, 2019;Müftüler, 2018;Nazlier Keser, 2019), social security (Emeksiz, 2019), views on the elderly (Birinci, 2018) and attitudes (Özgöl, 2019;Pehlivan & Vatansever, 2019), active aging (Canatan & Boz, 2019;Çapcıoğlu & Alpay, 2019;Görgün Baran & Kurnaz, 2019;Kırdı & Abit Kocaman, 2019). In addition to these studies, it is possible to come across studies (Canatan & Boz, 2019;Sınmaz & Erbey, 2019) that deal with gerontology and lifelong learning together (Bulaç & Kurt, 2019;Çatal, 2019).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is seen that they have tendency on the subjects such as; general health (Altunel & Kartal, 2019;Karadayı et al, 2019), care services (Çiftçi & Zelka, 2019;Müftüler, 2018;Nazlier Keser, 2019), social security (Emeksiz, 2019), views on the elderly (Birinci, 2018) and attitudes (Özgöl, 2019;Pehlivan & Vatansever, 2019), active aging (Canatan & Boz, 2019;Çapcıoğlu & Alpay, 2019;Görgün Baran & Kurnaz, 2019;Kırdı & Abit Kocaman, 2019). In addition to these studies, it is possible to come across studies (Canatan & Boz, 2019;Sınmaz & Erbey, 2019) that deal with gerontology and lifelong learning together (Bulaç & Kurt, 2019;Çatal, 2019).…”
Section: Related Literaturementioning
confidence: 99%
“…They concluded that lifelong learning activities contribute to older adults, from health to life satisfaction, from socialization to productivity, and intergenerational cooperation. In the study of Sınmaz and Erbey (2019), with the approach of reaching from the microscale to the macro scale, a model is proposed to provide active aging by measuring the interest-perception towards active aging in Balıkesir province. In the study, it was concluded that active aging is perceived as working again, the elderly do not want to work in a new job even if they are in economic distress, they do not have the strength and time for a new job, and they do not want to participate in activities such as hobbies.…”
Section: Studies Not Directly Related To the Studymentioning
confidence: 99%